Efektivitas Pelaksanaan Rehabilitasi Terhadap Pelaku Tindak Pidana Penyalahgunaan Narkotika - Ahmad M Ridwan Saiful Hikmat (JURNAL PEMULIAAN HUKUM, 2020)
With the issuance of Law Number 35 of 2009 concerning Narcotics, it is hoped that it can prevent and suppress the increase in the circulation and use of narcotics in the territory of Indonesia, including West Java. With a law that specializes in narcotics, all parties hope that it can run well and existing sanctions can be set fairly for perpetrators of narcotics crimes. Article 1 number 1 of Law Number 35 of 2009 concerning Narcotics means Narcotics are: substances or drugs derived from plants or non-plants, both synthetic and semi-synthetic which can cause a decrease or change in consciousness, loss of taste, reduce to eliminate pain, and can lead to dependence. In West Java there are about 800 thousand users, this can continue to increase every year with the age of the user from 10 to 59 years. The problem in the research is how effective is the implementation of rehabilitation for addicts and victims of narcotics abuse? And Are the obstacles and efforts to carry out rehabilitation for perpetrators of criminal acts of narcotics abuse related to the narcotics law? The type of study in this study is more descriptive analysis, because it intends to clearly describe the effectiveness of the implementation of rehabilitation for perpetrators of criminal acts of narcotics abuse associated with the narcotics law. Normatively, rehabilitation is regulated in Article 54 of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, following up on this matter, the Supreme Court Circular Letter (SEMA) Number 4 of 2010 was issued concerning the Placement of Abusers, Victims of Abusers in Medical and Social Institutions. To strengthen this, the government also issued Government Regulation (PP) Number 25 of 2011 concerning the Implementation of Compulsory Reporting of Narcotics Addicts to obtain therapy and Rehabilitation services.Dengan dikeluarkannya Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika, diharapkan dapat mencegah dan menekan meningkatnya peredaran serta penggunaan narkotika di wilayah Indonesia termasuk Jawa Barat. Dengan Undang-Undang yang mengkhususkan mengenai narkotika, maka semua pihak berharap dapat berjalan dengan baik dan sanksi yang ada dapat ditetapkan secara adil bagi pelaku tindak pidana narkotika. Pasal 1 angka 1 Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika pengertian Narkotika adalah: zat atau obat yang berasal dari tanaman atau bukan tanaman, baik sintesis maupun semi sintesis yang dapat menyebabkan penurunan atau perubahan kesadaran, hilangnya rasa, mengurangi sampai menghilangkan rasa nyeri, dan dapat menimbulkan ketergantungan. Di Jawa Barat ada sekitar 800 ribu pengguna, ini bisa terus meningkat tiap tahunnya dengan usia pemakainya dari 10 sampai 59 tahun. Permasalahan dalam penelitian yaitu Bagaimanakah efektifitas pelaksanaan rehabilitasi bagi pecandu dan korban penyalahgunaan narkotika? Dan Apakah kendala dan upaya pelaksanaan rehabilitasi terhadap pelaku tindak pidana penyalahgunaan narkotika dikaitkan dengan undang undang narkotika?. Tipe kajian dalam penelitian ini lebih bersifat deskriptif analisis, karena bermaksud menggambarkan secara jelas, tentang efektivitas pelaksanaan rehabilitasi terhadap pelaku tindak pidana penyalahgunaan narkotika dikaitkan dengan undang undang narkotika.Secara normatif rehabilitasi diatur dalam Pasal 54 Undang-Undang Republik Indonesia Nomor 35 Tahun 2009 tentang Narkotika, menindaklanjuti hal tersebut maka dikeluarkan Surat Edaran Mahkamah Agung (SEMA) Nomor 4 Tahun 2010 tentang Penempatan Penyalahguna, Korban Penyalahguna Kedalam Lembaga Medis dan Sosial. Untuk memperkuat hal tersebut maka pemerintah juga mengeluarkan Peraturan Pemerintah (PP) Nomor 25 Tahun 2011 tentang Pelaksanaan Wajib Lapor Pecandu Narkotika untuk mendapatkan layanan terapi dan Rehabilitasi.